TEACHER TALK AND INSTRUCTIONAL LANGUAGE CHOICE: TWO PROBLEMS ENCOUNTERED IN EFL CLASSROOM - Widya Rizky Pratiwi (Universitas Muhammadiyah Makassar, 2018)
When we agree with the internalization of a foreign language acquisition centered in the classroom, teacher talk plays the most important role to achieve the success of teaching and learning. However, a high intensity of teacher talk and the hesitation of instructional language choice become two common problems are usually faced. Therefore, it seems important to present a variety of literature reviews to be considered by teachers which may be used as the reference to solve the problem. This study presented the concept of teacher talk at classroom interaction, monolingual and bilingual approach in EFL classroom and some previous research findings “the rationales for supporting bilingual approach” which were gained from some articles. This study suggests that teachers have to control the quantity and quality of their talk to gain an effective teaching and learning process in the EFL classroom. It is more advantageous to reduce Teacher Talk Time and increase Student Talk Time based on the students’ need because too much teacher talk will have an impact on decreased student learning motivation. When teaching EFL students, it will be helpful for overcoming cognitive difficulties if teachers insert mother tongue for the certain condition such as to translate difficult words from reading the text and to explain grammar. However, the teachers have to keep a principled and judicious use of mother tongue because a very high proportion of it also limits the students’ achievement. If the students are exposed more to the second language, they will become more successful